Pengetahuan dan sikap ibu hamil dengan pola kepatuhan mengonsumsi tablet tambah darah di Kabupaten Aceh Timur - Devi Utari; Agus Hendra Al Rahmad (Jurnal SAGO Gizi dan Kesehatan, 2022)
Background: Pathological conditions from pregnancy to childbirth in a woman are essential to pay attention to watch out. One of them is anticipating chronic energy deficiency disorders in women. Adherence to the consumption of blood supplement tablets is still constrained due to mothers' low knowledge and attitudes.Objectives: The study aimed to measure the relationship between the knowledge and attitudes of pregnant women with adherence to taking blood supplement tablets in the East Aceh District.Methods: The research design was cross-sectional, involving a sample of 41 pregnant women, and was conducted in 2019 in East Aceh. Data collection on knowledge, attitude, and compliance were through direct interview techniques with questionnaire instruments. Data processing starts from editing, coding, entry cleaning, data entry, to tabulation. Data analysis using Chi-square statistical test at 95% CI.Results: Most pregnant women had good knowledge (58,5%) and attitudes (68,3%) about nutrition, anemia, and consumption of blood supplement tablets. Iron tablet consumption compliance was 70,7%. There was an association between knowledge (p= 0,035; OR= 4,4) and attitude (p= 0,018; OR= 5,4) with adherence to taking blood supplement tablets among pregnant women in East Aceh District.Conclusion: Good knowledge and attitude are related to the level of compliance of pregnant women in taking blood supplement tablets.